APPLICATION OF THE SEVEN PRINCIPLES OF SAPPAYA TO PROMOTE THE QUALITY OF LIFE OF THE ELDERLY - Moonthong, Phrapalad Nattapon; ., Phrakru Wijitsreerajal; ., Phrakru Kositwattananukul; Panasree, Sitthichok (Journal of MCU Nakhondhat, 2025)
Currently, Thailand has completely entered into an aging society. This is because factors such as population structure, economics, society, politics, and technological progress have come to play a role in the quality of life of Thai people. Especially the quality of life of the elderly society. Economic and social progress This causes the population structure and lifestyle of Thai people to change as well. Quality of life of the elderly is that the elderly is satisfied with their daily life appropriately in 4 areas: physical health, mental health, social relationships. and environmental. The seven principles of Sappaya include: 1) Arvas Sappaya, a comfortable place to live; 2) Kojara Sappaya, the village is comfortable; 3) Passa Sappaya, words that are comfortable; 4) Pukkala Sappaya, the person is comfortable. 5) Phochana Sappaya, Food is comfortable. 6) Utu Sappaya, the weather is comfortable, and 7) Iriyapatha Sappaya, the posture is comfortable. Application of the Seven principles of Sappaya to apply in real life of the elderly, especially both physically and mentally which is an important aspect for the elderly. That is, applying Dhamma principles to the lives of the elderly which in daily life. All 7 comforts must be taken into account, which is to get a suitable place for relaxation. Traveling is convenient. Negotiating with people who want, having friends who think about helping and supporting each other, having food that you can eat without getting bored, having pleasant weather or atmosphere and having done the physical exercise whether it is standing, walking, sitting, or lying down appropriately, it is one option that will ultimately give the elderly a better quality of life.